An Analysis of The English Summative Test: EFL Teacher-Made Test - Yessicka Noviasmy; Risma (Universitas Muhammadiyah Barru, 2024)
This study aims to determine the quality of the multiple-choice summative test items for senior high school EFL teachers in Parepare. The analysis consisted of validity, reliability, level of difficulty, and distractors. The type of research used in this research was quantitative descriptive. The subjects in this study were 33 students. The data in this study was collected using documentation techniques. Data analysis in the form of item analysis was carried out using the Biserial point correlation. The results of the study showed that the valid category was 80% and invalid are 20%. Included in the unreliable test with KR-20 < 0.70 or 0,6. The difficult category was 1 item, the moderate category was 8 items, and easy category was 1 item. Distractors function very good was 70%, good category was 20%, and the quite good category was 10%. It can be resumed that the final multiple-choice test made by EFL teacher has very good quality of item validity, unreliable test, good quality level of difficulty, and very good quality distractor. Based on the result analysis of test items, it can be concluded that several good test items can still be used for the future summative test, and several test items should be revised.